2010
DOI: 10.2105/ajph.2008.149542
|View full text |Cite
|
Sign up to set email alerts
|

The Disproportionate Cost of Smoking for African Americans in California

Abstract: Although African Americans account for 6% of the California adult population, they account for over 8% of smoking-attributable expenditures and fully 13% of smoking-attributable mortality costs. Our findings confirm the need to tailor tobacco control programs to African Americans to mitigate the disproportionate burden of smoking for this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Our results seem consistent with the observation that smoking cessation rates were higher among whites than African–Americans in recent years (6.0% vs 3.3% in 2010) 54. Given that African–Americans suffer a disproportionate burden of smoking-attributable mortality and healthcare costs,17 other non-price tobacco control programmes tailored to African–American smokers are needed to increase their cessation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results seem consistent with the observation that smoking cessation rates were higher among whites than African–Americans in recent years (6.0% vs 3.3% in 2010) 54. Given that African–Americans suffer a disproportionate burden of smoking-attributable mortality and healthcare costs,17 other non-price tobacco control programmes tailored to African–American smokers are needed to increase their cessation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Intensifying this issue, the has literature suggested that African Americans suffer a disproportionate burden of smoking-in California, African Americans accounted for 6% of the adult population, but they accounted for over 8% of smoking-attributable healthcare expenditures and 13% of smoking-attributable mortality costs. 40 Therefore, for a variety of reasons, it is essential to increase smoking cessation rates, especially among African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking-attributable healthcare expenditures for adults aged 18 years and older were estimated with the econometric models that Max and colleagues have developed and refined over the past 2 decades 22 23. The models use a prevalence-based annual cost approach and an excess cost methodology.…”
Section: Methodsmentioning
confidence: 99%